A formação do tradutor e intérprete de Libras para a atuação na saúde pública: discutindo sobre ações durante a pandemia de COVID-19 a partir do programa Informa-SUS - Caetano, David da Silva (Universidade Federal de São Carlos, 2021)
The work of the translator and interpreter of Brazilian Sign Language (Libras) comes being discussed in the country, in its different and diverse spheres of action, mainly since the beginning of the 2000s (BRASIL, 2002; 2005), from the recognition of sign language in Brazil and, more recently, the professionalization of the work of the translator/interpreter from Libras (BRASIL, 2010). In this context, the objective of this work is to highlight the performance of the translator and interpreter of Libras in the sphere of public health, with emphasis on specific training needs for that field. starting from a qualitative research approach, the work presents a survey bibliographic and discusses aspects of the training of the Libras translator and interpreter for the mediation of medical care for deaf people. in a second moment, we highlight some of the performance needs of this that have been accentuated by the current COVID-19 pandemic. Thus, the work presents a brief discussion on aspects and specifics of the role of the Libras translator/interpreter to assist the deaf person in sphere of health to then problematize remote care necessary in the current pandemic context, from the actions developed by the Informa-SUS – UFSCar program, developed throughout 2020.
The training of the Libras translator and interpreter to work in the public health: discussing actions during the pandemic of COVID-19 from the Informa-SUS program
Keywords: Tradução e interpretação em Libras; Saúde pública; Atendimento remoto em saúde; InformaSUS; CIENCIAS HUMANAS